PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT WIRAUSAHA (STUDI KASUS MAHASISWA PERGURUAN TINGGI EKONOMI DI PURWAKARTA) - Iman Sidik Nusannas (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
This research has the title "The Influence of Entrepreneurship Education and Family Environment on Entrepreneurial Interest (Case Study of College Students of Economics in Purwakarta)" compiled by Iman Sidik Nusannas. The growing interest in entrepreneurship is determined by many factors. But in this study there are two main factors that are considered to have a major contribution in growing the interest of one's entrepreneurship. In addition, this is strongly influenced by the adequate entry of information about the object of interest. Information on the success of a business raises an understanding to the public that the entrepreneur has a proven prospect of success. This study aims to examine how the Effect of Entrepreneurship Education and Family Environment on Entrepreneurial Interest (Case Study of Higher Education Economics Students In Purwakarta). Data collection was done through distributing questionnaires addressed to 96 students who had attended entrepreneurship education course by using Accidental sampling technique. To test the hypothesis, there are two tests that are T test (partial), F test (simultaneous) with the help of IBM SPSS software version 23. The results showed that the Entrepreneurship Education and Family Environment has a positive effect on Entrepreneurship Interest among students. Keywords : Entrepreneurship Education, Family Environment, and Interests Entrepreneurship